Einstieg in die Kreislaufwirtschaft: Integrative Planung von Produkten und Geschäftsmodellen - Scholtysik, Michel; Koldewey, Christian; Dumitrescu, Roman; Pierenkemper, Christoph; Hensen, Christian

A Data Map for Product Creation: Tasks, Data Flows, and IT-Systems from the Initial Idea to the Start of Production - Ködding, Patrick; Tissen, Denis; Koldewey, Christian (Proceedings of the 56th CIRP Conference on Manufacturing Systems, CIRP CMS ‘23)

A Framework For The Domain-Driven Utilization Of Manufacturing Sensor Data In Process Mining: An Action Design Approach - Brock, Jonathan; Rempe, Niclas; von Enzberg, Sebastian; Kühn, Arno; Dumitrescu, Roman (5th Conference on Production Systems and Logistics)

Conceptual Framework for Prescriptive Analytics based on decision Theory - Weller, Julian; Migenda, Nico; Wegel, Arthur; Kohlhase, Martin; Schenk, Wolfram; Dumitrescu, Roman (IEEE ADACIS 2023)

A Reference Process Model for Scenario-based Foresight - Ködding, Patrick; Koldewey, Christian; Dumitrescu, Roman (Proceedings of the XXXII ISPIM Innovation Conference)

Enhancing Risk Management for Digitalisation Projects in the Context of Socio-Technical Systems - Menzefricke, Jörn Steffen; Koldewey, Christian; Dumitrescu, Roman (The Digital Twin of Humans)

The Role of Design in interdisciplinary Product Development – Challenges, Research Approaches and Further Research needs - Stöhr, Bernd; Koldewey, Christian; Dumitrescu, Roman (Proceedings of the Design Society)
Abstract In global competition, companies are continuously searching for a competitive advantage. A growing number of companies have identified the design of their products as a major success factor. The promises for companies associated with outstanding design are extremely attractive, ranging from better customer experience to higher sales growth. But even though the advantages of design seem to be compelling, companies are still having difficulties in leveraging the benefits of design. In this paper, we want to identify the underlying challenges that explain this gap. We are especially interested in the role and challenges of design in interdisciplinary product development. Therefore, we perform a literature review that clarifies terminology, analyses research approaches and identifies challenges. We determine seven key challenges for design in interdisciplinary product development. Furthermore, we observe a limited scope of research approaches in the reviewed literature. Based on these findings, we propose three further research directions to strengthen the role of design in interdisciplinary product development in the future.

Designing Business Models for a Circular Economy - Scholtysik, Michel; Rohde, Malte; Koldewey, Christian; Dumitrescu, Roman (Proceedings of the Design Society)
Abstract The megatrend sustainability will significantly change the future value creation of manufacturing companies. Their current linear value creation models need to change to conform to the requirements of sustainability. To face the challenges the circular economy has emerged as a promising economic model. With the shift from a linear to a circular economy, companies have to adjust their current business models. However, they still lack knowledge and adequate methods to develop circular business models. Hence, the aim of the paper is a circular business model canvas (CBMC) for designing circular businesses. A systematic literature review was conducted to identify significant criteria for circular business models. The criteria were analyzed utilizing a qualitative content analysis to derive the business model elements required for the circular economy. Existing elements from the Business Model Canvas were enriched and five new elements, e.g., reverse logistics, were found. Then, the business model elements were logically arranged resulting in the CBMC. It guides companies to systematically develop business models for the circular economy. The CBMC was evaluated by applying it within a mediumsized company in the electronics sector.

Model-based Systems Engineering using Security Design Patterns in the Context of ISO/SAE 21434 - Japs, Sergej; Faheem, Faizan; Anacker, Harald; Husung, Stephan; Dumitrescu, Roman (Proceedings of the Design Society)
Abstract The development of modern vehicles is complex, especially regarding compliance with security and safety. ISO/SAE 21434 considers security and safety along the entire product life cycle. According to the standard, a system architecture, a risk analysis, and the application of countermeasures are carried out in the early system design. Design patterns are solutions to known design problems. Security Design Patterns (SDP) describe countermeasures and are used to reduce risk. After our literature review, we did not find a suitable approach that presents SDPs that would be applicable in early system design. In this paper, we present 10 SDPs for early system design, which we evaluated during an 11-week student project with 28 teams. We present the results of the quantitative analysis and the evaluation of the feedback.

TCO analysis of a modular and integral product architecture in shipbuilding - Seidenberg, Tobias; Disselkamp, Jan-Philipp; Jürgenhake, Christoph; Wicker, Ansgar; Dumitrescu, Roman; Tolo, Edmund

Future production of ships – case study for modular high-speed ferries - Disselkamp, Jan-Philipp; Seidenberg, Tobias; Jürgenhake, Christoph; Anacker, Harald; Dumitrescu, Roman

Towards a Data-Driven Product Management – Concepts, Advantages, and Future Research - Fichtler, Timm; Grigoryan, Khoren; Koldewey, Christian; Dumitrescu, Roman (2023 IEEE International Conference on Technology Management, Operations and Decisions (ICTMOD))
Megatrends, such as digitization or sustainability, are confronting the product management of manufacturing companies with a variety of challenges regarding the design of future products, but also the management of the actual products. To successfully position their products in the market, product managers need to gather and analyze comprehensive information about customers, developments in the products’ environment, product usage, and more. The digitization of all aspects of life is making data on these topics increasingly available – via social media, documents, or the internet of things from the products themselves. The systematic collection and analysis of these data enable the exploitation of new potentials for the adaption of existing products and the creation of the products of tomorrow. However, there are still no insights into the main concepts and cause-effect relationships in exploiting data-driven approaches for product management. Therefore, this paper aims to identify the main concepts and advantages of data-driven product management. To answer the corresponding research questions a comprehensive systematic literature review is conducted. From its results, a detailed description of the main concepts of data-driven product management is derived. Furthermore, a taxonomy for the advantages of data-driven product management is presented. The main concepts and the taxonomy allow for a deeper understanding of the topic while highlighting necessary future actions and research needs.
Keywords: Product Lifecyle Management (PLM); Data Analytics; Data-driven Design; Engineering Management; Lifecycle Data

Strategische Planung des Einstiegs in die Plattformökonomie - Özcan, Leon; Drewel, Marvin; Koldewey, Christian; Dumitrescu, Roman (Digitalisierung: Fallstudien, Tools und Erkenntnisse für das digitale Zeitalter)

acatech Maturity Index Smart Services - Dumitrescu, Roman; Riemensperger, Frank; Schuh, Günther; Biehler, Jan; Frey, Anna; Hocken, Christian; Koldewey, Christian; Kühn, Arno; Rabe, Martin; Schacht, Maximilian; Comans, Sebastian; Fichtler, Timm; et al.

Circular Product-Service-System Ideation Canvas – A Framework for the Design of circular Product-Service-System Ideas - Scholtysik, Michel; Rohde, Malte; Koldewey, Christian; Dumitrescu, Roman

Scenario-Based Foresight in the Age of Digital Technologies and AI - Ködding, Patrick; Koldewey, Christian; Dumitrescu, Roman (New Digital Work)

Scenario-based Foresight in the Age of Digitalization and Artificial Intelligence – Identification and Analysis of Existing Use Cases - Ködding, Patrick; Ellermann, Kai; Koldewey, Christian; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Integrating Domain Expertise and Artificial Intelligence for Effective Supply Chain Management Planning Tasks: A Collaborative Approach - Lick, Jonas; Schreckenberg, Felix; Sahrhage, Philipp; Wohlers, Benedict; Klöcker, Susanne; von Enzberg, Sebastian; Kühn, Arno; Dumitrescu, Roman (Artificial Intelligence, Social Computing and Wearable Technologies, Vol. 113)

Engineering und Management von System of Systems–Gestaltungskonzepte im SoS-Engineering - Günther, Matthias; Göllner, Denis; Heihoff-Schwede, Jörg; Anacker, Harald; Dumitrescu, Roman (Tag des Systems Engineering 2023)

Reifegradmodell zur Einführung von Systems Engineering–Systemdenken als Handlungsfeld - Wilke, Daria; Heitmann, Rebecca; Tekaat, Julian; Anacker, Harald; Dumitrescu, Roman (Tag des Systems Engineering 2023)